2017
DOI: 10.1016/j.agee.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from intensively managed peat soils in an arable production system

Abstract: We monitored annual CO 2 , N 2 O and CH 4 emissions from arable peat soils.  Emissions were dominated by CO 2 from SOM mineralization.  Cumulative N 2 O emissions were important, and CH 4 emissions negligible.  Total emissions generally increased with an increase in SOM content.  Intensive cultivation promotes loss of SOM and depletes the soil resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…Consistent with our results, some previous studies have also reported that 20-cm watertable increases do not significantly affect soil CH 4 fluxes (e.g., Couwenberg & Fritz, 2012;Turetsky et al, 2014). Additionally, the CH 4 flux rate was close to 0 in our study, agreeing with very low CH 4 emission measured in the field by others (−0.15 to 0.25 Mg CO 2 -eq ha −1 yr −1 ; Taft et al, 2017Taft et al, , 2018. Such low emissions are typically found at sites, where topsoil is unsaturated, indicating predominantly aerobic conditions To provide an effective and practical strategy to reduce peat oxidation and GHG losses from cultivated peatlands, further complementary aspects should be evaluated in future studies.…”
Section: Effect Of Cover Crop Incorporation and Watertable Managementsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our results, some previous studies have also reported that 20-cm watertable increases do not significantly affect soil CH 4 fluxes (e.g., Couwenberg & Fritz, 2012;Turetsky et al, 2014). Additionally, the CH 4 flux rate was close to 0 in our study, agreeing with very low CH 4 emission measured in the field by others (−0.15 to 0.25 Mg CO 2 -eq ha −1 yr −1 ; Taft et al, 2017Taft et al, , 2018. Such low emissions are typically found at sites, where topsoil is unsaturated, indicating predominantly aerobic conditions To provide an effective and practical strategy to reduce peat oxidation and GHG losses from cultivated peatlands, further complementary aspects should be evaluated in future studies.…”
Section: Effect Of Cover Crop Incorporation and Watertable Managementsupporting
confidence: 93%
“…Taft et al, 2017). Total GWP was dominated by N 2 O emissions (90-98%) after vetch incorporation but mainly affected by CO 2 emissions (46-80%) following rye input.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…It has been estimated that 35-100% of drained Histosol loss may be attributable to microbially mediated CO 2 production (Leifeld et al, 2011). The small net consumption of CH 4 in these soils does little to offset CO 2 loss, whilst N 2 O emissions can be substantial, forming approximately one third to one half of the total GHG budget (Taft et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that N2O emissions from organic soil may be enhanced by drainage (Martikainen et al, 1993;Taft et al, 2017). The response will appear within days, as shown by Aerts and Ludwig (1997) in an incubation study with an oscillating WT.…”
Section: Nitrous Oxide Emissions and Water Table Dynamicsmentioning
confidence: 88%